The Progressive Tradition in Canadian Literature - Frank, David (Labour / Le Travail, 2003)
The article reviews and comments on the book, "Progressive Heritage: The Evolution of a Politically Radical Literary Tradition in Canada," by James Doyle.
Keywords: BOOKS – Reviews; Canadian literature; DOYLE; James; Nonfiction; PROGRESSIVE Heritage: The Evolution of a Politically Radical Literary Tradition in Canada (Book)